Cancer and the LGBTQ Population: Quantitative and Qualitative Results from an Oncology Providers’ Survey on Knowledge, Attitudes, and Practice Behaviors - Christina L. Tamargo (Journal of Clinical Medicine, 2017)
Background: Despite growing social acceptance, the LGBTQ population continues to face barriers to healthcare including fear of stigmatization by healthcare providers, and providers’ lack of knowledge about LGBTQ-specific health issues. This analysis focuses on the assessment of quantitative and qualitative responses from a subset of providers who identified as specialists that treat one or more of the seven cancers that may be disproportionate in LGBTQ patients. Methods: A 32-item web-based survey was emailed to 388 oncology providers at a single institution. The survey assessed: demographics, knowledge, attitudes, and practice behaviors. Results: Oncology providers specializing in seven cancer types had poor knowledge of LGBTQ-specific health needs, with fewer than half of the surveyed providers (49.5%) correctly answering knowledge questions. Most providers had overall positive attitudes toward LGBTQ patients, with 91.7% agreeing they would be comfortable treating this population, and would support education and/or training on LGBTQ-related cancer health issues. Conclusion: Results suggest that despite generally positive attitudes toward the LGBTQ population, oncology providers who treat cancer types most prevalent among the population, lack knowledge of their unique health issues. Knowledge and practice behaviors may improve with enhanced education and training on this population’s specific needs.